ANALISIS KEPUTUSAN PEMBELIAN KONSUMEN MILENIAL PADA PROVIDER SMARTPHONE (STUDI PADA PENGGUNA PROVIDER SIMPATI) - Ardio Galang Prasetyo (2020)
This research is a quantitative study with the aim of analyzing or knowing the effect of social media marketing and brand image on purchasing decisions. The population used for this study is the millennial generation that uses the Simpati provider in East Jakarta. sampling of 50 respondents, with the sampling method non probability sampling and using purposive sampling technique. Collecting research data through distributing online questionnaires in the form of google form. This research data analysis technique used inferential analysis method through PLS (partial leasts square) with SmartPLS 3.2 software. The results of this study indicate that (1) Social Media Marketing has no significant effect on purchasing decisions. (2) Brand Image has a significant effect on Purchasing Decisions